2013
DOI: 10.3109/15376516.2012.748857
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of pectin against cadmium-induced testicular toxicity and oxidative stress in rats

Abstract: Cadmium has been classified as an environmental pollutant and human carcinogen. Pectin is a family of complex polysaccharides that function as hydrating agents and cementing materials for the cellulosic network. The aim of this study was to evaluate the protective role of pectin against cadmium-induced testicular toxicity and oxidative stress in rats. Forty male Wistar rats were divided into five equal groups. Groups 1 and 2 were injected intraperitoneally (i.p.) saline (1 mg/kg) and pectin (50 mg/kg), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Because the lipid peroxidation level was higher in the testes of Cd+EtOH‐treated animals than in the Cd‐treated rats, the antioxidant defence systems in the testes of these animals were much more disturbed compared to the Cd‐treated animals, but the testicular antioxidant defence system of the testis of these animals was able to cope with the altered oxidative balance and could not allow further peroxidative changes. It is usually reported that GSH level decreased after Cd treatment (Arafa, Mohammad, & Atteia, ; Jahan et al., ; Kheradmand, Alirezaei, & Dezfoulian, ; Koriem, Fathi, Salem, Akram, & Gamil, ; Pires et al., ). However, contrary results have observed that low Cd concentration increased GSH level, whereas high Cd concentration depleted GSH level (Gaubin et al., ), suggesting a relationship between tissue concentration of GSH and Cd (Thomas, Wofford, & Neff, ; Vogiatzis & Loumbourdis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the lipid peroxidation level was higher in the testes of Cd+EtOH‐treated animals than in the Cd‐treated rats, the antioxidant defence systems in the testes of these animals were much more disturbed compared to the Cd‐treated animals, but the testicular antioxidant defence system of the testis of these animals was able to cope with the altered oxidative balance and could not allow further peroxidative changes. It is usually reported that GSH level decreased after Cd treatment (Arafa, Mohammad, & Atteia, ; Jahan et al., ; Kheradmand, Alirezaei, & Dezfoulian, ; Koriem, Fathi, Salem, Akram, & Gamil, ; Pires et al., ). However, contrary results have observed that low Cd concentration increased GSH level, whereas high Cd concentration depleted GSH level (Gaubin et al., ), suggesting a relationship between tissue concentration of GSH and Cd (Thomas, Wofford, & Neff, ; Vogiatzis & Loumbourdis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some essential bioelements such as Ca, Fe, Mg and Zn may decrease liver accumulation of Cd by diminishing its absorption and availability for hepatocytes (Boujelben et al, ; Matović et al, ; Rogalska et al, ; Ryu et al, ; Sarić et al, ). In reference to the fact that the major mechanism of hepatotoxic action of Cd is its ability to generate FR and ROS, literature sources notably emphasize the possibility of using substances that may increase the antioxidative potential of hepatocytes and combat the adverse effects of Cd‐induced oxidative stress at the cellular level such as polyphenolic compounds, vitamins C and E, carotenoids, minerals, tannins, pectin and coenzyme Q10 (Figure ) (Brzóska, Borowska, & Tomczyk, ; Brzóska, Rogalska, et al, ; El‐Sayed et al, ; Gong et al, ; Koriem, Fathi, Salem, Akram, & Gamil, ; Mężyńska et al, ; Ognjanović et al, ; Winiarska‐Mieczan, ).…”
Section: Possible Strategies Of Protection and Treatment Of Cd‐inducementioning
confidence: 99%
“…Tannic acid was shown to prevent bones from Cd injury (Tomaszewska et al, 2017) and decrease the accumulation of this metal in the brain (Winiarska-Mieczan, 2013). The administration of pectin to rats improved the levels of antioxidants, decreased the concentration of MDA and ameliorated Cd-induced histopathological changes in the testes (Koriem et al, 2013). Moreover, owing to the chelating properties of dietary fiber (Borycka, 2012;Persson, Nyman, Liljeberg, Önning, & Frølich, 1991) consumption of fiber-rich food may also contribute to alleviate hepatotoxicity of Cd by decreasing gastrointestinal absorption of this metal and enhancing its elimination from the organism (Berglund et al, 1994).…”
Section: Other Ingredients Of Polyphenol-rich Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd can also induce hematological and biochemical toxicity [9], hepatotoxicity [45], nephrotoxicity [41,42], neurotoxicity [44] and testotoxicity [24,30]. Furthermore, Cd can induce several toxic effects in newly born rat pups on lactational exposure [13].…”
Section: Introductionmentioning
confidence: 99%